Sebuah KONTRAS KEHIDUPAN DAN MAKNA DALAM GAYA BAHASA THIBĀQ SYAIR IMAM SYAFI’I: KAJIAN STILISTIKA: KONTRAS KEHIDUPAN DAN MAKNA DALAM GAYA BAHASA THIBĀQ SYAIR IMAM SYAFI’I: KAJIAN STILISTIKA - Anisa Siti Muslimah; Ilyas Rifa'i (Bahasa dan Sastra Arab, Fakultas Adab dan Humaniora, UIN Sunan Gunung Djati, 2025)
This study explores the use of thibāq figurative language in the poetry of Imam al-Shāfiʿī, with a focus on the contrasts of life and meaning embedded within. Thibāq, as a rhetorical stylistic device, is employed to emphasize semantic oppositions through the use of lexically or contextually contrasting words or phrases. By analyzing three of Imam al-Shāfiʿī’s poems that center on themes of the worldly and the hereafter, knowledge and action, as well as life and death, this research aims to reveal how thibāq functions not only as an aesthetic element but also as a tool to reinforce moral and philosophical messages in classical Islamic literature. The method employed is stylistic analysis with a qualitative approach, identifying recurring thibāq patterns and their impact on the overall meaning of the poetry. The findings indicate that thibāq serves as a rhetorical device that enhances the moral and philosophical messages of the poems, while also contributing to their aesthetic value and expressive strength. This dualistic style deepens emotional resonance and enriches the overall meaning of the work. It is expected that this study contributes to the field of classical Arabic literary studies, particularly in understanding rhetorical techniques and the function of figurative language in conveying meaning. Keywords: Poetry, Stylistics, Thibāq